Community-based approaches to support the anchoring of climate-smart agriculture in Tanzania - Pamuk, Haki; van Asseldonk, Marcel; Wattel, Cor; Ng'ang'a, Stanley Karanja; Hella, Joseph Philip; Ruben, Ruerd (Frontiers in Climate, 2022)
We assess the impact of community-based approaches to promote adoption of integrated climate smart agriculture (CSA) practices based on soybean cultivation combined with mulching, intercropping, crop rotation, manure application and rhizobium inoculation methods. We use quasi-experimental data of farmers participating in Farmer Field Business Schools (FFBS) and Village Savings and Loan Associations (VSLAs) in Iringa region of Tanzania. Farmers received technical training and financial support for the initial adoption of soybean production, and women’s empowerment supported household’s continuous involvement in CSA practices. We find a positive effect for farmers participating in the trainings provided by the FFBSs and receiving microfinance services from VLSA members on the adoption rates of several CSA practices, and this effect became more pronounced for households with higher scores on women empowerment. Farm-level improvement in soybean production and market-level incentives for soybean sales should also strengthen household income, consumption and nutrition levels to maintain CSA practices. Community-based platforms create critical external conditions for introducing CSA practices, but women’s empowerment is indispensable for intrinsic incentives for anchoring their adoption.